2017
DOI: 10.1093/europace/eux291
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein stenosis or occlusion after catheter ablation of atrial fibrillation: long-term comparison of drug-eluting versus large bare metal stents

Abstract: The use of LD-BMS for the treatment of PVS/O was associated with an acceptable long-term outcome. Coronary DES implantation resulted in a high rate of restenosis and should therefore not be performed. Larger trials are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…20,21 However, limited data still suggest that outcome of DES alone is inferior to the larger diameter bare metal stents in this patient cohort. 22 It follows from our data that to improve outcomes of this patient cohort intervention should be undertaken before diffuse hypoplasia of the upstream pulmonary vein occurs. Previous data suggest time from ablation to intervention to be inversely associated with upstream pulmonary vein diameter.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…20,21 However, limited data still suggest that outcome of DES alone is inferior to the larger diameter bare metal stents in this patient cohort. 22 It follows from our data that to improve outcomes of this patient cohort intervention should be undertaken before diffuse hypoplasia of the upstream pulmonary vein occurs. Previous data suggest time from ablation to intervention to be inversely associated with upstream pulmonary vein diameter.…”
Section: Discussionmentioning
confidence: 87%
“…DES placement in both congenital PVS in small children and in adults after PVI shows promising results in small diameter vessels . However, limited data still suggest that outcome of DES alone is inferior to the larger diameter bare metal stents in this patient cohort …”
Section: Discussionmentioning
confidence: 91%
“…In one case series of 56 patients with RFA-induced PV stenosis, stenting was found to be 95.8% successful, with significantly improved pressure gradients, vessel caliber, and symptoms [ 13 ]. Bare metal stents (which were used in our patient) have been shown to have a lower rate of restenosis than drug eluting stents [ 14 ]. In addition to instent stenosis, other complications of PV interventions include PV rupture, stroke, and phrenic nerve injury, which are all exceedingly rare [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously our group demonstrated that stenting significantly reduced the risk of restenosis compared to treatment with balloon angioplasty alone . A recent cohort study by Fink et al of 25 PVS cases reported restenosis in veins treated with large‐diameter BMS (range 7.0–10.0 mm) was one third of that in the DES group (range 4.0–5.0 mm) (21 vs. 67%, p = .08) . This suggests stent diameter may be an important predictor of restenosis.…”
Section: Discussionmentioning
confidence: 81%